The A‐theoretic Farrell–Jones conjecture for virtually solvable groups. Issue 2 (28th December 2017) - Kasprowski, Daniel; Ullmann, Mark; Wegner, Christian; Winges, Christoph
Abstract: We prove the A ‐theoretic Farrell–Jones conjecture for virtually solvable groups. As a corollary, we obtain that the conjecture holds for S ‐arithmetic groups and lattices in almost connected Lie groups.